Strained c:Si0.55Ge0.45 with embedded e:Si0.75Ge0.25 S/D IFQW SiGe-pFET for DRAM periphery applications. (February 2016) - Ritzenthaler, R.; Schram, T.; Witters, L.; Mitard, J.; Spessot, A.; Caillat, C.; Hellings, G.; Eneman, G.; Aoulaiche, M.; Na, H.-J.; Son, Y.; Noh, K.B.; et al.
Abstract: In this work, we demonstrate a High-k Metal Gate (HKMG) Implant Free Quantum Well (IFQW) SiGe-pFET device used as a DRAM periphery device. Using a c:Si0.55 Ge0.45 channel and embedded e:Si0.75 Ge0.25 source/drain (S/D), a very significant source current of 625 μA/μm @ I OFF =100 pA/μm (at supply voltage V DD =−1 V) is demonstrated. The current improvement compared to DRAM compatible unstrained Silicon baseline technology (featuring HKMG) is large, and IFQW transistors are also competitive with regards to Strained Si devices. In particular, IFQW have a specific potential for Sense Amplifiers, with a demonstrated very good drive current/transconductance boost in the range of targeted gate lengths and excellent matching properties.